2023
DOI: 10.2147/ccid.s381471
|View full text |Cite
|
Sign up to set email alerts
|

Cemiplimab for the Treatment of Advanced Cutaneous Squamous Cell Carcinoma: Appropriate Patient Selection and Perspectives

Layna Mager,
Samantha Gardeen,
David R Carr
et al.

Abstract: Five percent of patients with cutaneous squamous cell carcinoma develop locally advanced or metastatic disease that is not amenable to definitive surgical or radiation therapy. Cemiplimab, an antibody against programmed death receptor-1, was approved in the United States for the treatment of locally advanced and metastatic cutaneous squamous cell carcinoma in 2018. We performed a literature review on the use of cemiplimab in cutaneous squamous cell carcinoma, with an emphasis on efficacy, safety and tolerabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Immunotherapy has transformed the management of severe cancers, including cutaneous squamous cell carcinoma (CSCC). Cemiplimab, which acts as a PD-1 immune checkpoint inhibitor, has been approved by the FDA for treating locally advanced and metastatic cutaneous squamous cell carcinoma (CSCC) [ 157 ]. This type of tumor frequently arises as a complication in patients who are chronically immunosuppressed following a transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy has transformed the management of severe cancers, including cutaneous squamous cell carcinoma (CSCC). Cemiplimab, which acts as a PD-1 immune checkpoint inhibitor, has been approved by the FDA for treating locally advanced and metastatic cutaneous squamous cell carcinoma (CSCC) [ 157 ]. This type of tumor frequently arises as a complication in patients who are chronically immunosuppressed following a transplant.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, the Food and Drug Administration (FDA) approved cemiplimab (LIBTAYO, Regeneron Pharmaceuticals Inc.), an antibody against programmed cell death receptor-1 (anti-PD-1), for such advanced skin SCC cases. Phase I/II clinical trials showed response rates between 42.9% and 50.8% for locally advanced and metastatic disease, and observational studies post-approval documented rates of 32-77% (median 58%) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous squamous cell carcinoma (CSCC) is the second most common nonmelanoma skin cancer, which accounts for 20% of all skin cancers [1]. While most CSCCs are treated with surgical intervention, approximately 5% display an aggressive phenotype that is not amenable to surgery or radiation therapy [2]. This paved the way for exploring immunotherapy options to treat advanced cases of CSCC.…”
Section: Introductionmentioning
confidence: 99%
“…The use of cemiplimab in laCSCC and mCSCC has shown excellent objective response rates with good tolerability [4][5][6]. Although cemiplimab shows good efficacy in patients with CSCC, it has been associated with side effects such as fatigue, diarrhea, anemia, rash, pruritus, musculoskeletal pain, pneumonia, and pancreatitis [2]. On rare occasions, cemiplimab can give rise to potentially life-threatening endocrinopathies such as diabetic ketoacidosis (DKA) [2].…”
Section: Introductionmentioning
confidence: 99%